Result of Validation of Electronic Learning Material for Newton's Law with Kvisoft Flipbook Maker for Class X High School Students - Dona Fitri Ayu; - Asrizal; - Festiyed; - Hidayati (Universitas Negeri Padang, 2021)
The 21st century is the century was technology have developed. The use of technology in education is highly demanded in the 21st century. Teacher can maximize the utilize of technology in the learning activities namely using learning material that utilize technology. The presence of learning material that utilize technology can increase the activeness of students in the learning activities so that can be done effectively. The fact found in school was that the learning material used by students was still low in the use of technology.This has an impact on student learning outcomes which ware still low seen from the average value of the mid-semester test for X Natural Science 1 students, namely 51,67. The alternative solution to overcome this problem in this study is to develop electronic learning material of the Newton's law with Kvisoft Flipbook Maker for class X high school students. This research has a purpose namely to know the validity of electronic learning material of the Newton's law. The learning material of the Newton's law with Kvisoft Flipbook Maker is used as object in this research which is limited to one class X. Research and development is a type of research that used in this research. Data collection instrument used was validity sheet. The research result found from the data analysis was validation of electronic learning material of the Newton's law is very good category. The value obtain was 89,43. So, it was can be stated that the electronic learning material of the Newton's law with Kvisoft Flipbook Maker is valid used in learning physics for class X high school students